The Influence of Giving Moring Capsules on Stress Levels In Pregnant Women - Hafid, Ridha; K, Sarinah Basri; Aulia, Ulfa (PT Inovasi Pratama Internasional, 2023)
Pregnant women can experience stress during pregnancy. Moringa leaves as nutrition during pregnancy. By administering Moringa leaf extract, stress in pregnant women can be reduced. The purpose of this study was to determine the effect of giving Moringa capsules on stress levels in pregnant women. The results showed that the pre test was 9.53 ± 2.41, the post test score was 3.97 ± 1.45, the EPDS score decreased 5.57 ± 2.51 and based on the results of the Pairet T Test statistical test (EPDS score) was obtained (p <0.001). There is an effect of giving Moringa capsules to pregnant women on reducing stress in pregnant women in Bone District, South Sulawesi Province. From the results of this study it is hoped that the raw material for Moringa leaves can be used as the main raw material in additional food products to improve the health of pregnant, lactating women and toddlers as an effort to reduce maternal mortality, infant mortality and make it a continuation of the GAMARA'NA program.